Prevention of acute kidney injury through accurate fluid balance monitoring. Issue 2 (25th November 2017) - Davies, Andrew; Srivastava, Seema; Seligman, William; Motuel, Lorraine; Deogan, Vardeep; Ahmed, Shaza; Howells, Nicholas
Abstract : Acute kidney injury (AKI) is associated with increased patient morbidity, mortality and an extended hospital stay. The financial burden to the National Health Service is high and it can affect up to one in five inpatients. Optimal fluid balance management is essential for the prevention of AKI and this can be particularly challenging in the patient with trauma. Our aim was to reduce the rate of AKI in patients with traumatic injuries in the regional trauma centre. We developed new fluid balance charts and documented how well these were completed. The number of AKI alerts per month was calculated on our pathology system. Scenario training was delivered at handover meetings and an e-learning tool was designed at three levels: healthcare assistants; nurses; and medical staff, dietetics and pharmacists. Educational posters were placed in clinical areas and patient information leaflets produced. Junior doctors were regularly informed of AKI rates on the ward. The number of AKI alerts on our trauma ward declined from 50 in January 2016 to 19 in November 2016. The mean monthly rate of AKI fell 33% following the invention (P<0.001). Completion of fluid balance charts improved; 6 hourly urine output documentation increased from 36% to 68% and running 1 hourly output increased from 80% to 96%. Calculation of total daily fluid balance rose from 12% to 72%, before decreasing to 32%. This highlighted the need for continued encouragement. Improved fluid balance monitoring led to a reduction in the prevalence of AKI in patients admitted to this trauma centre.